Pengembangan Model Pelatihan Sistem Manajemen Mutu Berbasis Website - Sofyan Sofyan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
The aims of this research are to develop a training model of a quality of web-based management system. The model development is employing Dick and Carey model. This model development step begins by identifying instructional goal(s), conduct instructional analysis, analyze learner and context, write performance objectives, develop assessment instrument, develop instructional strategy, develop and select instructional materials, design and conduct the formative evaluation of instructional, revising, and design and conduct a summative evaluation. Research and development produce web-based training model in the form of conceptual and physical models. Of the product development process and evaluation is done, it can be concluded, that the training model based quality management system and effectiveness websites categorized either to improve the competence of employees in providing services.